Pengaruh Penambahan Ekstrak Jeruk Nipis (Citrus Aurantifolia) sebagai Acidifier terhadap Performa Ayam Broiler - Pasi, Maria Selfiana; Agustina Viktoria Tae, Oktovianus Rafael Nahak; Viktoria Tae, Agustina; M C Noach, Steffanie; Hoar Klau, Delviana (Study Program of Animal Husbandry, Faculty of Agricultural, Universitas Majalengka, 2024)
Research was carried out to examine the effect of giving Citrus aurantifolia as an acidifier on growth in broiler. The research uses an experimental model with the application of a Completely Randomized Design (RCD). The treatments tested consisted of four treatments which were differentiated based on the level of use of Citrus aurantifolia in drinking water, namely without Citrus aurantifolia (T0), 25 ml/975 ml drinking water (T1), 50 ml/950 ml drinking water (T2), and 75 ml/925 ml drinking water (T3). Each treatment was repeated four times so that there were 16 experimental units, each experimental unit consisted of 5 broiler chickens so that a total of 80 chickens were used. The variables observed were body weight gain, feed consumption and feed conversion. Data analysis used analysis of variance (Anova) and Duncan’s multiple range test. The results showed that the increase in body weight for T0, T1, T2 and T3 was 103,13±3,72, 107,21±5,08, 112,31±073, 120,94±2,13 g/head. Feed consumption was 162,65±1.80, 165,82±0.49, 168,30 ±0.71, 170,36±0.23 g/head. Feed conversion was 1,58±0,05, 1,55±0,07, 1,50±0,01, 1,41±0,02 g/head. The result statistical analysis (Anova) showed that the treatment had a very significant effect (P>0,05) on body weigth gain, feed consumption and feed conversion of broiler. it was concluded that the addition of Citrus aurantifolia as an acidifier in drinking water can have a positive effect on body weight gain, feed consumption and feed conversion in broiler.